The Behavior of Muslim Investors in Choosing and Making Stock Investment Decisions in the Islamic Capital Market - Amelia Rahmawati; Hendri Hermawan Adinugraha; Drajat Stiawan (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2023)
The world of investment is an interesting topic of discussion, especially investing in the capital market. In general, people make investments to get a high enough return or profit from what is expected. This research uses the method of literature review or literature review in which data is obtained from various sources such as journals, books, documentation, and the internet during the last five years. The results of the study show that perceptions of behavioral control greatly influence investors' behavior in making investment decisions and attitudes towards perceived risk also influence investors' decision-making to invest.